Susan Glaspell and the anxiety of expression language and isolation in the plays - Hinz-Bode, Kristina 1971- (McFarland & Co., 2006)
"This work concentrates on one of Glaspell's central themes: individuality versus social existence. It explores the range of forces and fundamental tensions that influence the perception and communication of her characters. A biographical overview provides background for the author's reading and interpretation of the plays, placing Glaspell within the context of literary modernism"--Provided by publisher.